2020
DOI: 10.3390/ijerph17103459
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Aspects and Psychological Reactions to COVID-19 of Dental Practitioners in the Northern Italy Districts of Modena and Reggio Emilia

Abstract: The outbreak and diffusion of the Severe Acute Respiratory Syndrome-Coronavirus-2 (Sars-CoV-2) and COronaVIrus Disease 19 (COVID-19) have caused an emergency status in the health system, including in the dentistry environment. Italy registered the third highest number of COVID-19 cases in the world and the second highest in Europe. An anonymous online survey composed of 40 questions has been sent to dentists practicing in the area of Modena and Reggio Emilia, one of the areas in Italy most affected by COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
294
8
27

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(392 citation statements)
references
References 22 publications
38
294
8
27
Order By: Relevance
“…The present study showed a 10% prevalence of severe COVID-19-induced stress among dental academics; a higher level than the 7% reported among the general public in Wuhan, China [27] and 8.7% general anxiety reported among Italian dentists [28] and similar to the 11.5% among Israeli dentists and dental hygienists [40]. This indicates a need to provide support for dental academics' mental health.…”
Section: Factorssupporting
confidence: 50%
See 1 more Smart Citation
“…The present study showed a 10% prevalence of severe COVID-19-induced stress among dental academics; a higher level than the 7% reported among the general public in Wuhan, China [27] and 8.7% general anxiety reported among Italian dentists [28] and similar to the 11.5% among Israeli dentists and dental hygienists [40]. This indicates a need to provide support for dental academics' mental health.…”
Section: Factorssupporting
confidence: 50%
“…Countries from which participants were recruited are listed in S1 Appendix. Sample size was based on assuming a 95% confidence level, 5% margin of error, and prevalence of severe stress = 10% [27,28]. The calculated number of participants also ensured adequate power for Principal Component Analysis (PCA) which requires at least 100 participants [29].…”
Section: Participants and Samplingmentioning
confidence: 99%
“…31 Reporting information like this is essential to plan future prevention strategies. 10 The questionnaire was created using Google Forms and was sent via a link in a messaging app, e-mail and social media, and is in accordance with Iqbal et al 4 Consolo et al 32 also used Google Forms to create their survey, but they sent it via an anonymous e-mail. In this study, a messaging app was chosen because they are practical and can be accessed quickly by cell phone, which facilitates the healthcare workers' response.…”
Section: Discussionmentioning
confidence: 99%
“…Several surveys have been proposed since the spread of SARS-CoV-2 pandemic in order to assess the impact of coronavirus on dental activities, highlighting the great psychological distress among dental staff [ 17 , 18 , 19 , 20 ]. Nevertheless, it could be considered the fact that such questionnaires were delivered during a very sensitive moment of the pandemic, in which severe levels of anxiety could be found worldwide.…”
Section: Discussionmentioning
confidence: 99%